A new magneto-dynamic compression technique for magnetorheological elastomers at high frequencies. (April 2018) - Agirre-Olabide, I.; Elejabarrieta, M.J.
Abstract: A new magneto-dynamic compression technique was designed and manufactured to measure the magneto-viscoelastic properties of magnetorheological elastomers (MREs) at high frequencies. Isotropic MREs filled with carbonyl iron powder were synthesised, and three volumetric particle contents were studied—0%, 15% and 30%. Viscoelastic properties were calculated using stress–strain diagrams for each frequency and strain amplitude condition. The linear viscoelastic (LVE) region in compression mode was defined for MREs, and the influence of synthesis and characterisation variables in this region was analysed. Moreover, the compression magneto-viscoelastic properties were measured up to 200 Hz in the LVE region. Two types of tests were performed to characterise isotropic MREs in compression mode, a strain-sweep test to define the LVE region and a frequency-sweep test to study the magneto-viscoelastic properties in the LVE and at frequencies. The LVE region was determined at 0.3% by the higher particle content sample and at the lower frequency. Within the LVE region, the storage modulus and the loss factor increased with frequency and particle content. The compression magnetorheological (MR) effect increases with particle content and magnetic field density. Highlights: A new magneto-dynamic compression technique for magnetorheological elastomers (MREs) is presented. The linear viscoelastic (LVE) region is determined in compression mode for MREs. The LVE region in compression mode is larger than in shear mode. The magneto-viscoelastic properties at high frequencies of MREs are determined. The magnetorheological effect is larger in compression mode than in shear mode.